2012
DOI: 10.1111/j.1349-7006.2012.02274.x
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effect and pharmacokinetics of intraperitoneal NK105, a nanomicellar paclitaxel formulation for peritoneal dissemination

Abstract: The intraperitoneal administration of paclitaxel has been shown to be a promising treatment strategy for peritoneal malignancy. The present study evaluated the effects of intraperitoneal administration of NK105, a paclitaxel-incorporating micellar nanoparticle, which has been shown to have a remarkable effect in a mouse model of gastric cancer. Intraperitoneal NK105 significantly reduced peritoneal tumors in vivo compared with the conventional paclitaxel formulation of paclitaxel solubilized in Cremophor EL an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 51 publications
(82 reference statements)
0
18
1
Order By: Relevance
“…In our case, tumor burden of the mice treated with PTX-polymersomes was 8 times lower than in PTX-Cre group and 7 times lower compared with ABX. Remarkably, the total dose of PTX we used in our treatment was only 7 mg/kg - the lowest reported PTX dose used in experimental tumor treatment with free PTX or ABX (7,8,10,4446). The rationale for using the PTX dose below the MTD, with which the PTX-polymersomes are still effective, was to demonstrate that it is possible to reduce the PTX side effects while preserving therapeutic antitumor activity.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In our case, tumor burden of the mice treated with PTX-polymersomes was 8 times lower than in PTX-Cre group and 7 times lower compared with ABX. Remarkably, the total dose of PTX we used in our treatment was only 7 mg/kg - the lowest reported PTX dose used in experimental tumor treatment with free PTX or ABX (7,8,10,4446). The rationale for using the PTX dose below the MTD, with which the PTX-polymersomes are still effective, was to demonstrate that it is possible to reduce the PTX side effects while preserving therapeutic antitumor activity.…”
Section: Discussionmentioning
confidence: 91%
“…When PTX-polymersomes were used for experimental therapy of mice bearing IP MKN-45P gastric tumors, they showed potent anti-tumor activity, superior to ABX or PTX-Cre. It has been reported that in the treatment of MKN-45P mice with IP administered NK105 - a PTX-incorporating micellar nanoparticle formulation (8) - or a copolymer conjugated with PTX (10), the weight of peritoneal tumor nodules was ~ 5 times lower than in mice treated with PTX-Cre. In another study of IP treatment of ovarian tumors, dendrimer-based nanoparticles loaded with PTX reduced the growth of tumors about 5-fold more than ABX (7).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the enhanced permeability and retention (EPR) effect, which is known as selective accumulation of nanoparticle drugs by passive targeting is thought to be another reason (37). Through the EPR effect, nanoparticle drugs are retained for a long period in the systemic circulation, are easily extravasated from tumor vessels into the interstitium of tumor tissue, and accumulate there for longer periods than conventional small-molecule agents (38)(39)(40). On the basis of these findings, i.v.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, NK105 (PEG-P[Asp]-paclitaxel) showed an area under the curve significantly higher than paclitaxel alone between 0 and 48 h after iv. administration (191,000 ± 32,100 vs 1500 ± 108 ng·h/ml, respectively) [81]. Other formulations in clinical trials such as NK911 (PEG-P[Asp]-doxorubicin) have shown high accumulation in solid tumors in mice [16], and SP1049C (Pluronic L61, F127-doxorubicin) exhibited notable single-agent activity in patients with adenocarcinoma of the esophagus and gastroesophageal junction with high efficacy and fewer side effects compared with drug alone [82].…”
Section: Nanoparticles In Colorectal Cancer Therapymentioning
confidence: 91%